The Routledge international handbook of morality, cognition, and emotion in China
1 online resource.
Keywords: "This ground-breaking handbook provides multi-disciplinary insight into Chinese morality, cognition and emotion by collecting in one place a comprehensive collection of essays focused on Chinese morality by world-leading experts from more than a dozen different academic fields of study. Through fifteen substantive chapters, readers are offered a holistic look into the ways morality could be interpreted in China, and a broad range of theoretical perspectives, including ecological, anthropological and cultural neuroscience"--